Place of Marriage and Dispensation from Form: Canons 1118 and 1127 §2 - Pfnausch, Edward G (Roman replies and CLSA advisory opinions 1996, 1996)
We are in the process of revising our diocesan marriage policies and have obtained policies for mixed marriages from other dioceses. Several of those policies stipulate that, for permission to marry in a place other than a Catholic church, a dispensation from canonical form is always required. I think the place of marriage and dispensation from canonical form are two very different issues and that they should be dealt with separately. What do you think we should do?